Resistance upset welding of Zr-based bulk metallic glasses - Andreoli, Angelo Fernandes (2017)
Zr-based bulk metallic glasses represent an emerging important class of structural materials with interesting properties due to its amorphous nature. In this study, the structural and microstructural transformations to the heat-affected zone of a Zr-based bulk metallic glass welded by the resistance upset technology were investigated. X-ray diffraction, optical and scanning electron microscopy were used to characterize the base metal and the heat-affected zone. Vickers microhardness testing was performed to assess the mechanical response of the welded joints. The amorphous phase volume fraction measured along the welded joints shows no difference between the base metal and the heat-affected zone. It was possible to achieve a sound weld with no crystallization of the base metal by means of a proper variables setup.